IMPLEMENTATION OF THE DELONE & MCLEAN METHOD TO MEASURE THE SUCCESS OF THE PERFORMANCE ACCOUNTABILITY SYSTEM OF GOVERNMENT AGENCIES (SAKIP) APPLICATION IN SUPPORTING GOOD GOVERMENT, CASE STUDY : SUBANG DISTRICT GOVERMENT - Zakiah, Azizah; Haryanti, Aliviani Fabillah Nur; Utami, Tyas; Nurrahman, Aldi; Ritia, Rifal; Zamolistria, Muhammad Regia (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aims to determine and analyze the effectiveness of an information system carried out in the local government of Subang district using the Delone & McLean method. The effectiveness of an information system can be interpreted as a measure of the success of an information system by using system quality, information quality, service quality, usage, user satisfaction, and net benefits as variables. This study uses structural equation modeling (SEM) analysis with data collection using a questionnaire given to civil servants or non-civil servants who act as system users. The sample used in this study involved 17 employees in the Subang District Government.The Subang District Government is obliged to report and record the use of finance in one fiscal year which is useful as evaluation material for agencies. so that the Government Agency Performance Accountability System (SAKIP) plays an important role in facilitating the reporting of annual financial reports. The Performance Accountability System of Government Agencies requires a measure of success in its implementation so that the results of measuring success in this study can produce how effective the system and data accuracy are in supporting financial recording and reporting. The results of this study resulted in a conclusion stating that the application of SAKIP to the Subang District Government was effective. The success of SAKIP is influenced by the satisfaction of the users as well as the quality of the system. However, there are other success variables that need to be improved.